Development of Load Characteristic for The Main Engine and Its PLC Compatible Preparation in Cooperation with The Water Brake as The Generator - Matthias Markert; Hartmut Schmidt; Muhammad Faiz Rifqi Ardyatama (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2017)
Water brake can be used in any application where a load brake is required on a rotational load. In the engine industry, dynamometer is used in conjunction with a power source and instrumentation to determine engine HP, Torque, and Efficiency ratings with a high degree of accuracy. Water brake are proven durable designs which use water flowing through the absorber to create a load on the engine. Only the amount of water necessary to provide the load is required. Precise load control of the dynamometer is as simple as increasing or decreasing water volume flowing through the dynamometer absorption body. The controls ensure engine load remains stable throughout the duration of the test cycle. Torque, horsepower, RPM, and water temperature are displayed on highly accurate digital instrumentation. Computers can perform both sequential control and feedback control, and typically a single computer will do both in an industrial application. Programmable logic controllers are a type of special purpose microprocessor that replaced many hardware components such as timers and drum sequencers used in relay logic type systems. They can also analyze data and create real time graphical displays for operators and run reports for operators, engineers and management. Industrial control systems are usually used in all over in control system. A distributed control system refers to a control system in which the controllers are spread throughout the system and connect by networks. Smaller automation applications can be implemented with programmable logic controllers. This research basically is about designing a programmable logic controller compatible for dynamometer to control speed, power and torque of main engine. To test engine performance in the laboratory, the engine is coupled to a dynamometer. In this research dynamometer are used to measure speed, power and torque. One of the most essential role of the control engineer is tuning of controller. Hence the performance of the calculated controller parameters depends on the correctness of the identified process model developed from engine behavior.